2018
DOI: 10.1186/s40723-018-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding nutrition policies in Australian early childhood education and care services: a content and qualitative analysis

Abstract: Background Early childhood education and care (ECEC) settings have always been recognised as important sites of learning; however, with an increasing number of children attending these services their role in optimal infant and child health is increasingly significant (Petitclerc et al. 2017; Scully et al. 2017; World Health Organization (WHO) 2016a). In Australia, formal, approved ECEC services provide education and care for infants and children from birth to 5 years prior to school entry. The ECEC system incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Currently, ACT, QLD and NT have age-specific recommendations separating children three years and younger from those four years and older, while NSW separates those under two years [ 35 , 45 , 46 , 47 ]. Other researchers have also suggested benefits of separate feeding policies for the infant age group [ 62 ]. Menus could potentially reflect specific provision by ADG age group segmentation if online menu planning tools and health professional software algorithms were adjusted to accommodate these; however, the practicality for services to work with and operationalise such requirements would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, ACT, QLD and NT have age-specific recommendations separating children three years and younger from those four years and older, while NSW separates those under two years [ 35 , 45 , 46 , 47 ]. Other researchers have also suggested benefits of separate feeding policies for the infant age group [ 62 ]. Menus could potentially reflect specific provision by ADG age group segmentation if online menu planning tools and health professional software algorithms were adjusted to accommodate these; however, the practicality for services to work with and operationalise such requirements would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These differences made translation and adoption of a nationally consistent approach challenging. Previous research has found that childcare staff commonly rely on personal knowledge and that some services do not use evidence-based guidelines such as the ADG when determining nutritional adequacy of the food provided to children [ 62 , 63 ]. Moreover, poor awareness of jurisdictional guidelines and evidence-based recommendations have been identified at the service level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These guidelines within the National Quality Framework are not authoritative, but provide flexibility on how service providers might meet the Standards. 21 As demonstrated in table 1 , this guide describes best practice guidelines for education and care services, recommending staff use positive role-modelling behaviours, engage children in healthy eating conversations, use cooking experience to build knowledge, provide meals consistent with the Australian Dietary Guidelines, implement frequent opportunities for physical activity and role-model enjoyment by engaging in activities. 20 A combination of resources designed to support OSHC programmes in meeting quality area 2 will be used to guide the criteria within this study, including (1) Heart Foundation’s ‘Eat Smart, Play Smart’ manual, 22 (2) Nutrition Australia’s ‘Healthy eating in the National Quality Standards’ 23 and (3) the ‘Food and drink checklist for outside school hours care’.…”
Section: Methodsmentioning
confidence: 99%
“…These guidelines within the National Quality Framework are not authoritative, but provide flexibility on how service providers might meet the Standards 21. As demonstrated in table 1, this guide describes best practice guidelines for education and care services, recommending staff use positive role-modelling behaviours, engage children in healthy eating conversations, use cooking experience to build knowledge, provide meals consistent with the Australian Dietary Guidelines, implement frequent opportunities for physical activity and role-model enjoyment by engaging in activities.…”
mentioning
confidence: 99%